"Go hard or go home": exploring young people's knowledge, attitudes and behaviours of alcohol use and water safety in Western Australia using the Health Belief Model. Issue 3 (4th May 2021) - Abercromby, Meg; Leavy, Justine E; Tohotoa, Jenny; Della Bona, Malena; Nimmo, Lauren; Crawford, Gemma
ABSTRACT: Issue Addressed: Alcohol and participation in aquatic activities are major risk factors for drowning, amongst young adults. This study explored and mapped young people's knowledge, attitudes and behaviours regarding alcohol consumption and participation in aquatic activities using the Health Belief Model. Methods: Using a semi-structured guide, eight focus groups were conducted with young people, 18–24 years, in Perth (n = 41). Alcohol consumption and its combination with aquatic activity and media messages were discussed. Results: Participants reported having consumed alcohol and participated in water-based activities, typically during social events and celebrations. Participants identified key events, peer-presence and social acceptability of drinking as a cultural norm influencing young people's decisions around mixing alcohol consumption and water-based activity. Conclusions: Consumption of alcohol around water is common practice amongst young adults increasing their risk of drowning. Young people are aware of the risks but also see a range of benefits. To shift cultural norms regarding alcohol consumption, risk-taking and water-based activity, further research would be beneficial to examine young people's social influences. An intervention focus on young men may be beneficial given the overrepresentation of men in Western Australian fatal drowning statistics. So What? Findings support the emergence of an 'aquatic alcogenic environment'. Well-resourced, long-term interventions are needed including those targeting self-efficacy and that contain segmented messages as well as environmental and social supports to address the impact of impairment or increased risk-taking resulting from alcohol consumption in aquatic environments.